'Low sodium' diuresis and ileal loss in patients with ileostomies: effect of desmopressin. Issue 6 (June 1991) - Sutters, M; Carmichael, D J; Unwin, R J; Sozi, C; Hunter, M; Calam, J; Lightman, S L; Peart, W S
Abstract : Patients with ileostomies show an early diuresis when sodium restricted; this, together with an obligatory ileal sodium loss, predisposes them to severe salt and water depletion. The role of arginine vasopressin in this circumstance and whether it is natriuretic, or antinatriuretic, is unclear. There is also controversy over its likely effect on small bowel fluid reabsorption. We have examined the effect of the non-pressor (V2) synthetic vasopressin analogue 1-deamino-8-D-arginine (desmopressin) on renal and ileal sodium and water excretion in ileostomy patients during acute adaptation to a low sodium diet. Patients were studied on two separate occasions (nonrandomised) with and without the administration of desmopressin (0.75 micrograms intramuscular, three times a day). In eight subjects without desmopressin there was pronounced diuresis on the first low sodium day, associated with a fall in renal sodium excretion and no change in ileal output or composition. In five (of the original) subjects with desmopressin there was pronounced antidiuresis, no change in renal sodium excretion, and no change in ileal output or composition. In both studies rises in plasma renin activity and salivary aldosterone concentration lagged behind the early decline in renal sodium excretion. We have confirmed the phenomenon of 'low sodium' diuresis after sodium restriction in ileostomy patients and shown that it can be prevented by desmopressin. Desmopressin has no direct or indirect effect on renal sodium excretion or ileal fluid and electrolyte loss in humans.